The Disposal of Placenta among Indigenous Groups Globally: An Integrative Literature Review - Cecilia Moeti; Fhumulani Mavis Mulaudzi; Molatelo Melitah Rasweswe (Hindawi Limited, 2023)
Introduction. The placenta, or afterbirth, plays a vital role in supplying nutrients and oxygen via the umbilical cord. Western medicine sees the placenta as a medical waste and discards it after delivery. Meanwhile, indigenous groups observe rituals or ceremonies prior to their disposal since it bears sacred importance. Aim. The aim of the literature review is to review the current literature on indigenous methods of disposing placenta. Methods. Through the EBSCOhost search engine, the authors had access to the following databases: CINAHL; MEDLINE; E-Journals; Health Sources: Nursing/Academic Edition; Scopus; and African Journals Online. A manual search of the grey literature through Google Scholar and Google Search engines, as well as citation searching using reference lists, was also used. The following keyword searches came up: placental disposal, placental waste, placental release, indigenous placental disposal, traditional placental disposal, cultural placenta, and placental rituals. The authors followed the inclusion criteria of qualitative, quantitative, or mixed research articles or reports from experts and different organisations published between 2013 and 2022 in English. Findings. The following three themes with subthemes emerged in the context of this review paper: (1) placental consumption (increases milk production, prevents postpartum depression, and prevents postpartum bleeding); (2) placental burial (burial site determines the child's fate, protection of the child, and fertility); and 3). artifacts (memorabilia). Conclusion. Indigenous placental disposal methods have a significant value to Indigenous women globally. The rituals performed have a special meaning attached to them. It is important for Western medicine to respect and support indigenous placental disposal methods and ensure safe handling from the healthcare facilities to their homes.